Can a simple and cheap semen assessment help with fertility? - Amorim, G.B.A.G. [UNESP]; Oliveira, O.M. [UNESP]; Papa, F.O. [UNESP]; Dell'Aqua, J.A. [UNESP]; Alvarenga, M.A. [UNESP]; Freitas-Dell'Aqua, C.P. [UNESP] (Elsevier, 2025)
The objective of this study was to evaluate, using light microscopy and simple tests, the following parameters in stallion semen: total and progressive motility, plasma membrane integrity, and sperm morphology, and to determine which of these factors may interfere with fertility. The study utilized a diluent for sperm evaluation based on Eosin and Nigrosin (Botuvital-Botupharma, Botucatu, Brazil), which allows the analysis of sperm pathologies and visualization of plasma membrane integrity under light microscopy. A total of 24 batches of frozen semen from 24 Arabian and Straight Egyptian Arabian stallions were used. Seen was frozen at different locations in Europe and the Middle East, and used for AI in Doha, Qatar. The straws contained the same concentration pattern of 100 million sperm cells. Each batch was thawed at 37°C for 1min, total and progressive motility were evaluated using light microscopy at 40X magnification, Botuvital was used to assess sperm morphology and membrane integrity. A total of 200 cells per sample was evaluated (at 100Xmagnification), and those with a pink head were classified as having a damaged plasmatic membrane. For sperm morphology, using the same light microscope, 200 cells per sample were categorized into major, minor, total, and non-compensatory defects. For AI, mares were examined once per day by transrectal ultrasonography (Mindray DP50 ultrasound with transrectal probe - frequency 5mHz). When a follicle ≥35mm was detected along with uterine edema, a single dose (1ml) of histrelin acetate (250µg, intramuscular, Strelin, Botupharma, Brazil) was administered. Deep-horn uterine insemination was performed 36-40 hours after ovulation induction using an equine universal flexible pipette. A single AI was performed on each mare on top of ovulation, and stallion groups were separated based on whether pregnancy was confirmed or not at 14 days by ultrasound. Parameters were assessed for normality using the Kolmogorov-Smirnov test, variables that showed normal distribution were compared using the unpaired T-test and non-parametric were compared using the Mann-Whitney test, with P<0.05 considered significant. Major sperm pathologies (P=0.0252), total sperm pathologies (P=0.0189), and non-compensatory defects (P=0.0099) - pathologies that cannot be compensated by increasing sperm concentration (Saacke.Theriogenology.2008) - showed statistically significant differences, while total motility, progressive motility, and membrane integrity did not show significant differences between animals that had confirmed pregnancies and those that did not. In conclusion, morphologically abnormal sperm are a critical component in the analysis of semen quality, and this highlights the efficiency of a quick and inexpensive assessment of sperm morphology, which can be conducted in the field.